Left heart remodelling in hypertensive patients: a comprehensive echocardiography and computed tomography study - Lange, Aleksandra; Palka, Viktoria; Bian, Chris; Huntress, Harry; Morgan, Jill; Allwood, Sean; Swann, Rohan; Palka, Przemysław (Frontiers in Cardiovascular Medicine, 2023)
Objectives This study aimed to assess left heart remodelling changes in hypertension, excluding underlying ischaemic heart disease, utilising computed tomography coronary angiography (CTCA) and transthoracic echocardiography (TTE). Methods A total of 178 patients (mean age 60 ± 9 years, 53% female) were enrolled in the study: Group 1 consisted of patients with essential hypertension (n = 96, Group 1), and Group 2 served as age-matched controls (n = 82, Group 2). All participants underwent both CTCA and TTE. TTE measurements included left ventricle (LV) concentricity and function and left atrial (LA) volume and function. Using both CTCA and TTE, we measured LV diastasis volume (LVdias) and LA diastasis volume (LAdias). Results LV mass index and LV mass/height2.7 were similar in both the groups. However, Group 1 had a higher prevalence of concentric LV remodelling, characterised by a larger mean LV wall thickness, increased relative wall thickness ratio, and a reduced ratio of LV end-diastolic volume (LVED) index to mean wall thickness (55 ± 14 vs. 65 ± 15, p = 0.0007). Group 1 showed higher LAdias and LA minimal volumes, while LA reservoir function was lower in Group 2. The LVdias/LAdias ratio was lower in Group 1 compared to Group 2 (TTE 1.77 ± 0.61 vs. 2.24 ± 1.24, p = 0.0025, CTCA 1.50 ± 0.23 vs. 1.69 ± 0.41, p = 0.0002). A composite score based on four combined TTE parameters, namely, LVED index/mean wall thickness ≤57, ratio of early diastolic mitral inflow to mitral annular tissue velocities (E/e’) >8, LVdias/LAdias ≤1.62, and LA reservoir function ≤0.58, yielded the highest discriminatory power (area under the curve—AUC = 0.772) for distinguishing patients with hypertensive heart disease (HHD). Collectively, we refer to these parameters as the LEDA score, with each parameter scored as one point. For LEDA scores of 0, 1, 2, 3, 4, the probability of underlying HHD was 0%, 23%, 59%, 80%, and 95%, respectively. Furthermore, a CTCA-derived LVdias/LAdias ≤1.76, considered as a single parameter, demonstrated modest accuracy in differentiating patients with HHD (AUC = 0.646). Conclusions The TTE LEDA score, based on four parameters, namely, LVED index/mean wall thickness, E/e’, LVdias/LAdias, and LA reservoir function, proved to be the most effective in defining left heart remodelling in hypertension.